Empowering Arabic Speaking Skills through Master of Ceremony (MC) Training: A Humanistic Approach - Habib, Moh. Tohiri; Fadhel Mubarak (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Abstract: Public speaking is a crucial skill in foreign language learning, fostering confidence and communicative competence. This study explores the impact of Master of Ceremony (MC) training as a pedagogical tool to enhance Arabic speaking proficiency through a humanistic approach. While previous research has highlighted anxiety and lack of self-confidence as barriers to Arabic language acquisition, limited studies have examined the role of structured MC training in overcoming these challenges. This research employs a qualitative case study approach, conducted at Pondok Pesantren Darullughah Wadda’wah (Dalwa), where Arabic serves as both a medium of instruction and daily communication. Data collection includes classroom observations, semi-structured interviews, and student self-reflections, analyzed thematically to identify linguistic and psychological developments. A total of 30 students with varying proficiency levels and 5 Arabic instructors participated in the study over an eight-week period. The research framework is grounded in Krashen’s Input Hypothesis and Vygotsky’s Sociocultural Theory, emphasizing meaningful language exposure and social interaction. Findings indicate that MC training significantly enhances students' confidence, fluency, and spontaneous speech production. Participants reported improved pronunciation, structured speech patterns, and greater motivation to engage in public speaking. Additionally, the study reveals a shift in students’ perception of Arabic from a rigid academic subject to a practical communication tool. Compared to traditional speaking exercises, MC training provides real-world communicative experiences, reducing reliance on memorization and fostering linguistic autonomy. This study contributes to Arabic language pedagogy by advocating performance-based learning as an effective strategy to bridge the gap between classroom instruction and real-life communication. The findings provide valuable insights for language educators, curriculum developers, and policymakers in integrating MC training into Arabic language programs. Keywords: Arabic speaking skills, MC training, humanistic approach, communicative competence, public speaking. ?????? ?????: ??????? ?????? ???? ??????? ?????? ?????? ?? ???? ?????? ????????? ?? ????? ????? ?????? ???????? ?????????. ???? ??? ??????? ??? ??????? ??? ??????? ??? ??? "???? ?????" (MC) ????? ?????? ?????? ????? ?????? ?????? ??????? ?? ???? ???? ??????. ???? ????? ?? ?? ?????? ????? ?? ???? ????? ??? ????? ????? ???? ????? ?????? ?????? ???? ?????? ????? ???????? ??? ?????? ?? ???????? ?????? ??? ??????? ?????? ??? MC ?? ?????? ??? ??? ????????. ????? ??? ??????? ??? ???? ????? ?????? ???????? ??? ?????? ?? ???? ??? ????? ??????? ????????? (????)? ??? ??????? ????? ??????? ?????? ??????? ???????? ??????. ???? ????? ??? ????????: ??????? ????? ??????? ??? ?????? ??????? ????? ??????? ??? ??????? ????????? ????? ?? ???????? ??????? ????????. ???? ?? ??????? ?????? ?????? ?? ??????? ??????? ????? ?????? ???? ???????? ??? ??? ????????????. ????? ??????? ??? ????? ?????? ?????? ?????? ?????? ???????? ???????? ??????????? ?? ??????? ??? ????? ?????? ??????? ???? ???????? ?????????. ????? ??????? ?? ????? MC ????? ???? ???? ?? ????? ??? ?????? ???????? ??????? ??? ?????? ????????. ??? ???? ????????? ????? ?? ?????? ?????? ??????? ??????? ???????? ?????? ???? ???????. ????? ???? ??????? ?? ???? ?? ???? ?????? ???? ???????? ?? ????? ???? ???????? ????? ??? ???? ????? ????. ?????????? ?? ???????? ????????? ?? ??????? ???? ????? MC ????? ????? ?????? ???? ?? ???????? ??? ????? ???????? ??????????? ???????. ??????? ??? ??????? ??????? ?? ????? ????? ??????? ?? ???? ?????? ??? ?????? ?????? ??? ?????? ??????????? ?????? ???? ?????? ??? ??????? ????? ???????? ???????. ?????? ??????? ??? ????? ????????? ?????? ???????? ????? ?????? ?? ???? ????? ????? ???????. ??????? ?????????: ?????? ?????? ????????? ????? MC? ?????? ????????? ??????? ?????????? ?????? ???? ???????.